2017
DOI: 10.1007/s00425-017-2693-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of VQ motif-containing proteins in Moso bamboo (Phyllostachys edulis)

Abstract: 29 Moso bamboo VQ proteins were genome-wide identified for the first time, and bioinformatics analysis was performed to investigate phylogenetic relationships and evolutionary divergence. The qRT-PCR data show that PeVQ genes response to different stress treatments. Accumulating evidence suggests that VQ motif-containing proteins in rice (Oryza sativa), Arabidopsis (Arabidopsis thaliana), and maize (Zea mays) play fundamental roles in response to various biotic and abiotic stresses. However, little is known ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 56 publications
5
58
0
Order By: Relevance
“…Structural predictions indicated that most NtVQ genes (83.1%) in tobacco lack introns (Supplementary Figure S1), consistent with VQ protein gene structure in other plants (e.g., 88.2%, 90%, and 92.3% of the VQ protein genes in Arabidopsis [11], Chinese Cabbage [14], and tomato [24], respectively, lack introns). It was reported that a large number of introns might be lost in VQ genes during evolution [18]. The distribution of NtVQ genes among clades based on protein sequence conservation appears to follow the pattern observed in other plant species as well.…”
Section: In-silico Analysis Of Ntvq Genesmentioning
confidence: 59%
See 3 more Smart Citations
“…Structural predictions indicated that most NtVQ genes (83.1%) in tobacco lack introns (Supplementary Figure S1), consistent with VQ protein gene structure in other plants (e.g., 88.2%, 90%, and 92.3% of the VQ protein genes in Arabidopsis [11], Chinese Cabbage [14], and tomato [24], respectively, lack introns). It was reported that a large number of introns might be lost in VQ genes during evolution [18]. The distribution of NtVQ genes among clades based on protein sequence conservation appears to follow the pattern observed in other plant species as well.…”
Section: In-silico Analysis Of Ntvq Genesmentioning
confidence: 59%
“…Analysis of the phylogenic tree of tobacco VQ proteins has shown that the clades are similar to those described for Arabidopsis [11] and tomato [24]. Tobacco NtVQ protein has an average of 223.5 amino acids, which is similar to the known VQ protein in many plants, where most of the VQ genes encode fewer than 300 amino acids, including Arabidopsis [11], rice [12], maize [16], Moso bamboo [18], apple [20], poplar [15], Chinese Cabbage [14], soybean [22], tomato [24], tea [23], and so on. On the contrary, four genes (NtVQ11, NtVQ12, NtVQ20, and NtVQ23) encode protein of more than or equal to 400 amino acids.…”
Section: In-silico Analysis Of Ntvq Genesmentioning
confidence: 75%
See 2 more Smart Citations
“…Bioinformatic analysis of TcNAC gene sequences and the calculation of coding sequence (CDS) length, molecular weight (MW), isoelectric point (pI), and open reading frame (ORF) lengths was performed using the Compute pI/MW tool at the Expert Protein Analysis System (ExPAsy) site (http://au.expas y.org/tools/pi_tool.html). We used the GSDS (Gene Structure Display Server) tool to analyze the exon/intron organization for individual NAC genes of Theobroma cacao [41,42]. MEME (v.12.0; http://meme-suite.org/tools/meme) was used to analyze the motifs of TcNAC proteins with the following parameters: minimum width of motifs, six; maximum width of motifs, 50; and number of motifs, 10.…”
Section: Sequence Analysis and Structural Characterizationmentioning
confidence: 99%